Poland, Sibir and Siberia: The Case of Igor Newerly. On the novel "The Hill of the Blue Dream" - Kopeć, Zbigniew (Porównania, 2024)
The subject of the article is the issue of the 1986 novel entitled The Hill of the Blue Dream by Igor Newerli. Its main character is a terror-accused political exile associated organizationally with the PPS Proletariat, and ideologically with the Warsaw radical intelligentsia of the early century, including Krzywicki, Abramowski, Sempołowska. The main scion of the novel’s plot is set in Siberia. The author of the novel is interested in the ethnostereotypes presented in the novel, such as, for example, the Siberian, the Russian, the Buryat. He analyzes the genre conventions and plot solutions present in the novel. He also answers the question of how the dark sides of socialist-conspirator life, such as suspicions of treason, permeate into the Siberian Arcadia in which the protagonist lives. The author of the article looks at the book from two perspectives: the time in which it is set – the first decades of the 20th century, and the place and time of its publication. It is Poland of the second half of the 1980s plunged into marasmus and hopelessness ruled by authorities linked to the USSR.